Urgensi Pemberian Izin Pengelolaan Tambang bagi Organisasi Kemasyarakatan "Keagamaan" di Indonesia: Analisis Regulasi dalam PP Nomor 25 Tahun 2024 - Prastika, Amanda; Mutiara Fajriatul Izza Putri; Viorelia Nabila Tasya (Taruna Law: Journal of Law and Syariah, 2024)
Government Regulation No. 25/2024 on the Amendment to Government Regulation No. 96/2021 on the Implementation of Mineral and Coal Mining Business Activities has sparked heated debate in Indonesia. One of the controversial points is the provision that allows religious community organizations to obtain mining business licenses, which is contrary to Law No. 3 of 2020 concerning Mineral and Coal Mining. The writing of this research uses normative legal research methods that emphasize in-depth study of laws and regulations that exist in society. This research was conducted to find out how the form of decisions on mass organizations that apply for licenses in PP No. 25 of 2024 and how efforts to apply for WIUPK by mass organizations according to PP No. 25 of 2024 and Law No. 3 of 2020. The research that will be outlined in the form of this article is entitled "The Urgency of Granting Mining Management Permits for "Religious" Mass Organizations in Indonesia: Regulatory Analysis in Government Regulation Number 25 of 2024" aims to examine these provisions in depth. This journal will analyze the urgency of granting mining permits for religious mass organizations, with an emphasis on the regulatory aspects contained in PP No. 25 of 2024.